1978
DOI: 10.1210/jcem-47-2-354
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Hypothyroidism and Maternal Thyroid Status in Severe Endemic Goiter*

Abstract: The relationship between maternal thyroid function and newborn thyroid function was studied in a region of very severe endemic goiter (Ubangi, Republic of Zaïre). T4, T3, and TSH concentrations were measured in the sera of 56 mothers (at the time of delivery) and 60 newborns (in the cord). The results obtained in these groups (untreated) were compared with those obtained in two control groups, comprising 53 mothers whose iodine deficiency had been corrected by the injection of iodized oil and 68 neonates born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
7

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 15 publications
(18 reference statements)
3
67
1
7
Order By: Relevance
“…The results of the present experiments show that this mechanism is indeed operative in the neonatal rat, because T3 was maintained within normal limits in the face of markedly decreased (<10% of The weight of the animals is given in Table V. IOP, 10 mg/100 g bw, was injected intraperitoneally 40 Table III. § P < 0.01 with respect to A.…”
Section: Resultsmentioning
confidence: 53%
“…The results of the present experiments show that this mechanism is indeed operative in the neonatal rat, because T3 was maintained within normal limits in the face of markedly decreased (<10% of The weight of the animals is given in Table V. IOP, 10 mg/100 g bw, was injected intraperitoneally 40 Table III. § P < 0.01 with respect to A.…”
Section: Resultsmentioning
confidence: 53%
“…The trial from Zaire further revealed that administration of iodized-oil injections was effective in reducing infant mortality and improving neurologic outcome even when given in midpregnancy. [207][208][209] community-based evidence. Apart from the data from Zaire and Papua New Guinea, our search identified 1 additional community-based trial of iodine supplementation (Table 9).…”
Section: Iodine Supplementationmentioning
confidence: 99%
“…The most extensive available data on thyroid function during pregnancy in populations with an I intake below 25 µg/d are from New Guinea (Choufoer et al 1965;Pharoah et al 1984) and the Democratic Republic of Congo (RDC; former Zaire; Thilly et al 1978;Delange et al 1982).…”
Section: Thyroid Function In the Mothersmentioning
confidence: 99%